Optimizing the Use of Mobile Banking Service Systems in Attracting Customer Interest at PT Bank Syariah Indonesia - Arif, Zainal; Zahira, Hasna; Zen, Muhamad (Yayasan Mitra Peduli Indonesia, 2022)
This research aims to determine the optimization of the use of the mobile banking service system in attracting customers' interest. Then, to find out the optimization process carried out by PT Bank Syariah Indonesia KCP Bogor Cileungsi Metland in the m-banking service system to attract customers to use it and the obstacles that arise. There is a solution to it. This study uses qualitative methods with descriptive analysis techniques to collect and find data through observation, interviews, documentation, websites, and books to obtain information and evidence in the research process. As a result, this study received results regarding optimizing the use of the mobile banking service system to attract these customers' interest by introducing more details to customers when opening accounts or other transactions. Then, promote well with advertisements, social media, and other exciting promotions. In addition, the constraints and solutions made by PT Bank Syariah Indonesia KCP Bogor Cileungsi Metland in optimizing the use of mobile banking are usually related to offline applications and depositing funds. The key is to make a report to the nearest branch and notify in detail about the problem until the customer understands.